1997
DOI: 10.1152/ajprenal.1997.273.4.f563
|View full text |Cite
|
Sign up to set email alerts
|

Early role of Fsp1 in epithelial-mesenchymal transformation

Abstract: A seamless plasticity exists among cells shifting between epithelial and mesenchymal phenotypes during early development and again later, in adult tissues, following wound repair or organ remodeling in response to injury. Fsp1, a gene encoding a fibroblast-specific protein associated with mesenchymal cell morphology and motility, is expressed during epithelial-mesenchymal transformations (EMT) in vivo. In the current study, we identified several cytokines that induce Fsp1 in cultured epithelial cells. A combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
362
1
6

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(395 citation statements)
references
References 77 publications
23
362
1
6
Order By: Relevance
“…35 Although these myofibroblasts are generally presumed to derive from local activation of residential fibroblasts under diseased conditions, evidence suggests that these cells may also derive from tubular epithelial cells via a process known as epithelial to mesenchymal transition. 36,37 Consistent with this view, our preliminary results show that TGF-␤1 can induce ␣SMA expression in both cultured renal interstitial fibroblasts and tubular epithelial cells in vitro (unpublished data). Regardless of the mechanisms, the fact that exogenous HGF inhibits myofibroblast activation in the obstructed kidneys underscores that exogenous HGF precisely targets a key event, the activation of principal matrix-producing cells, during renal fibrogenesis.…”
Section: Figure 7 Exogenous Hgf Inhibits Tgf-␤1 and Tgf-␤ Type I Recesupporting
confidence: 70%
“…35 Although these myofibroblasts are generally presumed to derive from local activation of residential fibroblasts under diseased conditions, evidence suggests that these cells may also derive from tubular epithelial cells via a process known as epithelial to mesenchymal transition. 36,37 Consistent with this view, our preliminary results show that TGF-␤1 can induce ␣SMA expression in both cultured renal interstitial fibroblasts and tubular epithelial cells in vitro (unpublished data). Regardless of the mechanisms, the fact that exogenous HGF inhibits myofibroblast activation in the obstructed kidneys underscores that exogenous HGF precisely targets a key event, the activation of principal matrix-producing cells, during renal fibrogenesis.…”
Section: Figure 7 Exogenous Hgf Inhibits Tgf-␤1 and Tgf-␤ Type I Recesupporting
confidence: 70%
“…For example, in both cultured epithelial cells and a transgenic mouse model of metastatic breast cancer, S100A4 expression was activated during EMT; antisense oligonucleotides suppressed S100A4 expression and epithelial transformation. 39,40 Furthermore, recently it was shown that for colon carcinoma cell lines S100A4 was a direct target of the Wnt/b-catenin pathway. Specific knockdown of S100A4 in this system significantly reduced the migratory ability of these cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…S100A4 [19], also known as fibroblast-specific protein 1 (FSP1) [20,21], is a member of the S100 superfamily of EF-hand calcium-binding proteins. P4HD is an essential enzyme for the biosynthesis of procollagen [22] and HSP47 is an ER-resident stress protein that is believed to function as a molecular chaperone specific to the biosynthesis of procollagen [23,24].…”
Section: Endmt Process In Afmentioning
confidence: 99%